Letter to Jane Tolmach from Senator Henry M. Jackson - Henry M. Jackson:::::: (1961)
A letter to Jane Tolmach from Senator Henry M. Jackson. The letter thanks Jane for her recent letter and inviting him tio a fund raising dinner after his adjournment of Congress.